Early disc degeneration in radiotherapy-treated childhood brain tumor survivors - Grahn P; Remes T; Kivisaari R; Suo-Palosaari MH; Arikoski PM; Koskenkorva PKT; LahteenmSki PM; Lonnqvist TRI; Ojaniemi MK; Sirkia K; Sutela AK; Toiviainen-Salo SM; et al. (BMC, 2025)
Background
Childhood brain tumor (BT) survivors have an increased risk of treatment-related late effects, which can reduce health-related quality of life and increase morbidity. This study aimed to investigate lumbar disc degeneration in magnetic resonance imaging (MRI) in adult survivors of radiotherapy-treated childhood BT compared to age and sex-matched population controls.
Methods
In this cross-sectional comparative study, 127 survivors were identified from hospital registries. After a mean follow-up of 20.7 years (range 5-33.1), 67 survivors (mean age 28.4, range 16.2-43.5) were investigated with MRI and compared to 75 sex-matched population-based controls. Evaluated MRI phenotypes included Pfirrmann grading, , intervertebral disc protrusions, extrusions, and high-intensity-zone-lesions (HIZ). Groups were also compared for known risk factors of lumbar intervertebral disc (IVD) degeneration.
Results
Childhood BT survivors had higher Pfirrmann grades than controls at all lumbar levels (all p < 0.001). Lumbar disc protrusions at L4-5 (p = 0.02) and extrusions at L3-4 (p = 0.04), L4-5 (p = 0.004), and L5-S1 (p = 0.01) were significantly more common in the BT group compared to the control. The survivor cohort also had significantly more HIZ-lesons than the controls (n=13 and n=1, p=0.003). Age at diagnosis was associated with lower degree of IVD degeneration (p < 0.01). Blood pressure correlated with IVD degeneration (P < 0.05).
Conclusions
Signs of early disc degeneration related to tumor treatment can be seen in the IVDs of survivors. Disc degeneration was more severe in children treated in adolescence.